Comparative analysis of triarylamine and phenothiazine sensitizer donor units in dye-sensitized solar cells. Issue 15 (6th February 2017) - Chiykowski, Valerie A.; Lam, Brian; Du, Chuan; Berlinguette, Curtis P.
Abstract : The performance of a homologous set of dyes that differ only in the donor fragments, namely phenothiazine (PTZ) and triarylamine (TPA) units, was evaluated in dye-sensitized solar cells (DSSCs). Abstract : A homologous set of dyes that differ only in the donor fragments, namely phenothiazine (PTZ) and triarylamine (TPA) units, were evaluated in dye-sensitized solar cells (DSSCs). The novel PTZ-based dye differs from the TPA-based dye in that it contains a sulfur bridge that planarizes two aromatic rings and enables higher dye loading and higher stability in the oxidized form. These positive features notwithstanding, the superior absorptivity of devices sensitized by TPA-based dyes resulted in significantly higher power conversion efficiencies (PCEs) than those sensitized by PTZ-based dyes.